Employee engagement - Bridger, Emma (Kogan Page, 2015)
"Achieving employee engagement is crucial to the success and continued high performance of any organization. But with budgets tighter than ever before, economic struggles and an increasingly stressful workplace for staff, this has become a difficult task.Aimed at HR practitioners and managers Employee Engagement offers a complete, practical resource for understanding, measuring and building engagement. With a focused approach on Positive Psychology, it also offers case studies, practical tools, techniques and diagnostics to help assess and drive engagement in an organization. "--Resumé vydavatele
Keywords: personální management; pracovní motivace; organizační chování; personnel management; employee motivation; organizational behavior; příručky; případové studie; handbooks and manuals; case studies